2017
DOI: 10.5194/nhess-17-2365-2017
|View full text |Cite
|
Sign up to set email alerts
|

Planar seismic source characterization models developed for probabilistic seismic hazard assessment of Istanbul

Abstract: Abstract. This contribution provides an updated planar seismic source characterization (SSC) model to be used in the probabilistic seismic hazard assessment (PSHA) for Istanbul. It defines planar rupture systems for the four main segments of the North Anatolian fault zone (NAFZ) that are critical for the PSHA of Istanbul: segments covering the rupture zones of the 1999 Kocaeli and Düzce earthquakes, central Marmara, and Ganos/Saros segments. In each rupture system, the source geometry is defined in terms of fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…3,[51][52][53][54] Furthermore, recent GMMs constrained with data from the region 55 we investigate in this study to reveal a great similitude to NGA-W2 GMMs, for magnitudes close to M w 7. With respect to the geometry of the fault, we use reported fault traces in the Marmara region, 56 to constrain the fault plane as shown in the yellow line in Figure 6.…”
Section: Description Of the Earthquake Source Methodsmentioning
confidence: 99%
“…3,[51][52][53][54] Furthermore, recent GMMs constrained with data from the region 55 we investigate in this study to reveal a great similitude to NGA-W2 GMMs, for magnitudes close to M w 7. With respect to the geometry of the fault, we use reported fault traces in the Marmara region, 56 to constrain the fault plane as shown in the yellow line in Figure 6.…”
Section: Description Of the Earthquake Source Methodsmentioning
confidence: 99%
“…This special issue includes 11 papers focused on data gathering (García-Mayordomo et al, 2017;Hintersberger et al, 2018;Jomard et al, 2017) as well as seismic and surface rupture hazard modelling (Avital et al, 2018;Valentini et al, 2017;Chartier et al, 2017a, b;Gülerce et al, 2017;Azzaro et al, 2017;Peruzza et al, 2017;Boncio et al, 2018).…”
Section: Published: 15 May 2018mentioning
confidence: 99%
“…Pace et al: Preface: Linking faults to seismic hazard assessment in Europe 6. Gülerce et al (2017) provide a seismic source characterization model used in the probabilistic seismic hazard assessment for Istanbul (Turkey).…”
Section: Published: 15 May 2018mentioning
confidence: 99%
“…Building on the findings of these studies, several earthquake rate forecast (ERF) models and hazard maps have been developed (Erdik et al, 2004;Gülerce et al, 2017;Murru et al, 2016;Sesetyan et al, 2018;Demircioglu et al, 2018). While these studies improve our understanding of the hazard for Istanbul, none of them fully explore the epistemic uncertainties in the parametrization of the ERF parameters that have the potential to affect the seismic hazard in Istanbul.…”
Section: Introductionmentioning
confidence: 99%
“…It has long been observed that the number of earthquakes in a region decreases with the magnitude of the earthquake. Gutenberg and Richter (1944) established the logarithmic decrease in the number of earthquakes with the magnitude (noted as GR law hereafter). However, the possibility for the seismicity on individual faults to follow a different type of MFD has been discussed, notably in California where several studies have discussed this aspect of earthquake statistics along the San Andreas strike slip fault systems, arguing either for the GR law (Page and Felzer, 2015) or for a discrepancy (Schwartz and Coppersmith, 1984).…”
Section: Introductionmentioning
confidence: 99%